Improving the Recruitment and Retention of Healthcare Professionals in Rural Areas: Evidence from the medical doctors of six districts of India - Manas Ranjan Behera; Hannah M. Degge; Ranjit Kumar Dehury; Deepanjali Behera (ACHSM, 2023)
Background: The Human Resource in Health (HRH) crisis is one of the most critical constraints to achieving health and development goals. In this study, the WHO's recommendations were used to highlight the health workforce issues in remote and rural areas with a prime focus on four major policy domains: education, regulatory, financial incentives, and professional and personal support. Objectives: Medical doctors are one of the essential frontline health workers for primary health care in rural India. This study adopted World Health Organization's (WHO's) human resource policy framework to evaluate doctors' responses in understanding the recruitment and retention of medical doctors in rural areas. Materials and Methods: A cross-sectional, descriptive study was conducted in the rural and remote areas of Odisha state, India. A multistage sampling procedure was used to select the participants, who were all government medical doctors working in rural and remote locations. The primary outcome measure is percentage responses using WHO's Human Resource policy framework Results: Medical doctors working in rural and remote areas perceived the practice as challenging. They were mainly least satisfied with the items asked in the professional and personal support domain. However, more than half of the doctors (56.7%) are eager to work in remote and rural areas for the next three years. Conclusion: Public health administrators and policymakers should create an enabling environment and design interventions encouraging doctors to stay in remote areas. Most importantly, this includes a political and financial commitment to achieve targeted interventions.